Transcriptomics and interactomics during the primary infection of an SfNPV baculovirus on Spodoptera frugiperda larvae - Rangel-Núñez, Jonatan Carmen; Ibarra, Jorge E.; Del Rincón-Castro, Ma. Cristina (Frontiers in Cellular and Infection Microbiology, 2023)
The fall armyworm (FAW), Spodoptera frugiperda, has been the most devastating pest of corn as well as of other crops in America, and more recently in Africa and Asia. The development of resistance to chemical insecticides led the search for environmentally friendly biological alternatives such as baculoviruses. This study focuses on the primary infection of the baculovirus SfNPV-Ar in the FAW’s midgut epithelium, by analyzing the differential expression of transcripts in excised midguts at 6, 12, and 24 h post-infection (hpi), and predicted their interactions. Interaction of viral factors with the infected midgut tissue could alters various cellular processes, such as the apoptotic system due to the up-regulation observed of FABP at 6 hpi and of HSP90 at 24 hpi, along with the down-regulated PRX at 6 hpi and FABP transcripts between 12 and 24 hpi. Changes in transcript regulation could affect the cellular architecture of infected cells due to up-regulation of ARP 2/3 at 6 and 12 hpi, followed by down-regulation at 24 hpi. In relation to protein folding proteins, HSP90 was up-regulated at 24 hpi and PDI was down-regulated between 6 and 12 hpi. With respect to metabolism and cellular transport, AcilBP and ATPS0 were up regulated at 6 hpi and 12 hpi, respectively. In reference to transcription and translation up-regulation of RPL11 at 6 hpi and of FPN32 and RPL19 at 24 hpi was detected, as well as the down-regulation of RPL19 at 6 hpi, of PDI and RPL7 at 12 hpi, and of FABP at 24 hpi. In conclusion, gene regulation induced by viral infection could be related to the cytoskeleton and cellular metabolism as well as to oxidative stress, apoptosis, protein folding, translation, and ribosomal structure. The results presented in this work are an approach to understanding how the virus takes control of the general metabolism of the insect host during the primary infection period.